Relationship of Thyroid Hormones with Heart Rate Variability - Kabir, Rassel; Begum, Noorzahan; Ferdousi, Sultana; Begum, Shelina; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2010)
Background: Altered thyroid functions are associated with variation in autonomic regulation of cardiovascular activity. Cardiac Autonomic Nervous Activity (CANA) can be assessed quantitatively by analysis of Heart Rate Variability (HRV). Objective: To observe the relationship between CANA with altered TSH and FT4. Methods: This cross sectional study was carried out in the Department of Physiology, BSMMU, Dhaka between1st July 2007 and 30th June 2008 on 60 patients with excess thyroid hormone (group B, aged 30-50 years). Based on treatment, 30 untreated newly diagnosed patients were designated as group B1 and 30 patients under treatment with antithyroid drugs for at least 2 months were included into group B2 in order to observe the effect of treatment. All these patients were selected from the Out Patient Department of Endocrinology wing of Department of Medicine, BSMMU, Dhaka. Sociodemographically matched 20 apparently healthy euthyroid persons were selected for comparison (group A). To confirm thyroid status, serum TSH and serum FT4 levels were measured by AxSym system and some of the spectral HRV parameters i.e.mean R-R interval, mean heart rate, variance, LF n.u, HF n.u and LF/HF ratio were assessed by recordings of ECG for 5 minute (short term) with a polyrite. For statistical analysis Pearson’s correlation coefficient (r) test was used. Results: With serum TSH level, the LF n.u. power and LF/HF ratio showed significant (p<0.05) positive correlations but HF n.u. power showed significant (p<0.05) negative correlation in group B1. But these three parameters showed non significant correlations with TSH in the other two groups (A, B2). Similarly with serum TSH level, variance and mean R-R interval showed negative and mean HR showed positive correlation in group B1. In group A, all these parameters were positively correlated whereas in group B2, RR interval and variance were positively and mean HR was negatively correlated. All these correlations were statistically non significant. With serum FT4 levels, mean R-R and HF n.u. were negatively and mean heart rate, LFnu, LF/HF were positively correlated in all three groups but variance showed positive in group A and negative correlation in B1 and B2. All these correlations were statistically non significant. Conclusion: From this study it can be concluded that changes in autonomic nervous regulation are related to altered serum level of TSH and FT4 in hyperthyroids. Key words: HRV; LF; HF; RR interval; Hyperthyroid DOI: 10.3329/jbsp.v5i1.5414 J Bangladesh Soc Physiol. 2010 June; 5(1): 20-26